Scaling Up Climate Services for Farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Participants in the December 2012 Scaling Up Climate Services for Farmers in Africa and South Asia workshop in Senegal visited the Kaffrine research site, where farmers received climate forecasts for the first time in 2011 through a CCAFS project.